Wake up your creative genius - Hanks, Kurt (Crisp Pub. Menlo ParkUS, 1991)
Suggests sources of good ideas and provides proven techniques that can multiply the quantity and quality of creative thoughts. Recommendations include: exercise your mind - ask questions; identify needs and create solutions; record sleep time ideas (dreams); invest creative effort; nurture new ideas patiently; learn from failure; and protect ideas legally. Also identifies some enemies of creativity, viz. inability to identify major pitfalls of an idea/product; inflexibility; fear of failure; and theft of ideas.